The emerging role of norepinephrine in cognitive dysfunctions of Parkinson's disease - Vazey, Elena; Aston-Jones, Gary (Frontiers in Behavioral Neuroscience, 2012)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder, affecting 1% of the population over age 60. In those patients cognitive dysfunction is a persistent issue that impairs quality of life and productivity. Neuropathological studies demonstrate significant damage in brain regions outside the nigral dopamine (DA) system, including early degeneration of locus coeruleus norepinephrine (LC-NE) neurons, yet discussion of PD and treatment focus has remained dopaminergic-based. Motor symptoms benefit from DA replacement for many years, but other symptoms including several cognitive deficits continue unabated. Recent interest in non-DA substrates of PD highlights early involvement of LC-NE neurons and provides evidence for a prodromal phase, with cognitive disturbance, even in sporadic PD. We outline insights from basic research in LC-NE function to clinical and pathological evidence highlighting a role for NE in PD cognitive dysfunction. We propose that loss of LC-NE regulation, particularly in higher cortical regions, critically underlies certain cognitive dysfunctions in early PD. As a major unmet need for patients, research and use of NE drugs in PD may provide significant benefits for cognitive processing.